The multifunctional gut of fish - Grosell, Martin; Farrell, Anthony Peter, 1952-; Brauner, Colin J. (Fish physiology, 2011)
The Multifunctional Gut of Fish provides a comprehensive synthesis and an integrative overview of the range of gut functions and their implications for organismal physiology. The highly diversified anatomy and functions of the gut, including nutrient uptake, immune barrier function, salt and water homeostasis and respiration, as well as neuroendocrine actions and control are covered in detail by leading authors. In addition, this volume explores the pronounced implications of gut function for whole animal integrative physiology and compensatory demands for non-gastrointestinal organs. As the first comprehensive reference to discuss the diverse morphological and functional adaptations of the gut, this volume provides an excellent resource for comparative physiologists, aquaculturists and biomedical researchers employing fish as model organisms for mammalian physiology. Includes chapters dedicated to anatomical and functional features of the gastro-intestinal tract of fish as well as integrative aspects of gut organ function. Includes in depth coverage of recently recognized implications of feeding on salt homeostasis and acid-base balance. Provides syntheses of implications of gut function for homeostasis. Essential text for those interested in the wide diversity of functions performed by the gut.